2011
DOI: 10.1088/0004-637x/727/1/53
|View full text |Cite
|
Sign up to set email alerts
|

Red Supergiant Stars in the Large Magellanic Cloud. I. The Period-Luminosity Relation

Abstract: From previous samples of Red Supergiants (RSGs) by various groups, 191 objects are assembled to compose a large sample of RSG candidates in LMC. For 189 of them, the identity as a RSG is verified by their brightness and color indexes in several nearand mid-infrared bands related to the 2MASS JHKs bands and the Spitzer /IRAC and Spitzer /MIPS bands. From the visual time-series photometric observations by the ASAS and MACHO projects which cover nearly 8-10 years, the period and amplitude of light variation are a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 65 publications
(128 reference statements)
6
64
1
Order By: Relevance
“…Kiss et al (2006) and Percy & Khatu (2014) identified periods of a few hundred to a few thousand days with varying stellar lightcurve morphology for RSGs in the AAVSO International Database. Such pulsations have also been observed occurring in RSGs within the Small and Large Magellanic Clouds (Feast et al 1980;Ita et al 2004;Szczygie l et al 2010;Yang & Jiang 2011;Yang & Jiang 2012;Yang et al 2018), M31 and M33 (Soraisam et al 2018;Ren et al 2019), M51 (Conroy et al 2018), M101 (Jurcevic et al 2000), within HST archival data of NGC 1326A, NGC 1425, and NGC 4548 (Spetsieri et al 2019), and within the GAIA DR2 RSG sample (Chatys et al 2019). These works identify these RSG pulsations Corresponding author: J.…”
Section: Introductionmentioning
confidence: 69%
“…Kiss et al (2006) and Percy & Khatu (2014) identified periods of a few hundred to a few thousand days with varying stellar lightcurve morphology for RSGs in the AAVSO International Database. Such pulsations have also been observed occurring in RSGs within the Small and Large Magellanic Clouds (Feast et al 1980;Ita et al 2004;Szczygie l et al 2010;Yang & Jiang 2011;Yang & Jiang 2012;Yang et al 2018), M31 and M33 (Soraisam et al 2018;Ren et al 2019), M51 (Conroy et al 2018), M101 (Jurcevic et al 2000), within HST archival data of NGC 1326A, NGC 1425, and NGC 4548 (Spetsieri et al 2019), and within the GAIA DR2 RSG sample (Chatys et al 2019). These works identify these RSG pulsations Corresponding author: J.…”
Section: Introductionmentioning
confidence: 69%
“…To explore the relation between photometric and spectral variations in both MCs, we have used the works of Yang & Jiang (2011, 2012. They studied the photometric variability of a large number of RSGs taken mainly from the same source as our sample (Massey 2003).…”
Section: Spectral Variabilitymentioning
confidence: 99%
“…HII regions can be isolated by their much redder K s −A colors, while measurements in the four IRAC bands distinguish between RSGs, O-rich and C-rich AGBs. Yang & Jiang (2011) revised the pulsation properties of RSGs in the LMC using a comprehensive list of 191 RSGs (Buchanan et al 2009). Only 24% of RSGs show regular pulsation (Yang & Jiang 2011 So far, little work has been done on Galactic evolved stars based on GLIMPSE data.…”
Section: Introductionmentioning
confidence: 99%
“…Yang & Jiang (2011) revised the pulsation properties of RSGs in the LMC using a comprehensive list of 191 RSGs (Buchanan et al 2009). Only 24% of RSGs show regular pulsation (Yang & Jiang 2011 So far, little work has been done on Galactic evolved stars based on GLIMPSE data. WRs have an infrared excess, due to free-free emission from dense stellar winds (Cohen et al 1975).…”
Section: Introductionmentioning
confidence: 99%